Hydrogen-Permeability of Titanium-Nitride (TiN) Coatings Obtained via the Plasma-Immersion Ion Implantation of Titanium and TiN Vacuum-Arc Deposition on Zr-1%Nb Alloy - Le Zhang; Nikitenkov N. N. Nikolai Nikolaevich; Sutygina A. N. Alina Nikolaevna; Kashkarov E. B. Egor Borisovich; Sypchenko V. S. Vladimir Sergeevich; Babikhina (Babihina) M. N. Mariya Nikolaevna (2018, 2018)
Title screen